Moral conflicts of organ retrieval : a case for constructive pluralism - Hinkley, Charles C. (Value inquiry book series ;, 2005)
This book addresses ethical conflicts arising from saving the lives of patients who need a transplant while treating living and dead donors, organ sellers, animals, and embryos with proper moral regard. Our challenge is to develop a better world in the light of debatable values and uncertain consequences.